Medieval Thought from a Fresh Perspective. Arlig, A. W. (2023). Medieval Philosophy: A Contemporary Introduction. New York: Routledge. - Shymanovych, Andrii (Sententiae, 2024)
Review of Arlig, A. W. (2023). Medieval Philosophy: A Contemporary Introduction. New York: Routledge.